Return to sport after forearm fractures in children: A scoping review and survey. (April 2023) - Bhanushali, Ameya; Bright, Rebecca; Xu, Louis; Cundy, Peter; Williams, Nicole
Purpose: A common question faced by clinicians is when a child may return to sport after treatment for a pediatric forearm fracture. There are few published recommendations and fewer supported by evidence. The aims of this study were to summarize existing published recommendation for return to sport after pediatric forearm fractures and to conduct a survey to determine usual clinical recommendations. Methods: A scoping review was performed on Ovid MEDLINE, Cochrane Central Register of Controlled Trials, Embase, Scopus, and Google Scholar in accordance with the Joanna Briggs Institute guidelines. In addition, 64 orthopedic surgeons were anonymously surveyed asking for recommendations regarding return to sport after pediatric forearm fractures. Participants were to assume children were 9 years old and played a sport with an average risk of forearm injury. Results: Twenty-two publications for return to sport were retrieved. Children with distal radius buckle fractures safely commonly returned to sport by 4 weeks after initial injury, while survey respondents recommended over 6 weeks. Survey respondents valued fracture stability the highest when making return to sport recommendations. Children with simple, metaphyseal, single-bone fractures were usually allowed to return to sport at 8–10 weeks post-injury. Diaphyseal and complete fractures were prescribed longer return to sport intervals. Australian respondents also prescribed longer return to sport intervals. Conclusion: Children with distal radius buckle fractures may return to sport by 4 weeks after initial injury, sooner than recommended. Published recommendations remain limited for other fractures. However, our survey suggests children with simple, metaphyseal, single-bone fractures may return to sport at 8–10 weeks. Children with diaphyseal and complete fractures should abstain from sport for longer than metaphyseal and greenstick fractures, respectively. Level of evidence: level V